Assessment of exercise-induced stress by automated measurement of salivary cortisol concentrations within the circadian rhythm in Japanese female long-distance runners - Tsunekawa, K.; Ushiki, K.; Shoho, Y.; Martha, L.; Ishigaki, H.; Matsumoto, R.; Yanagawa, Y.; Nakazawa, A.; Yoshida, A.; Nakajima, K.; Araki, O.; Kimura, T.; et al. (Sports Medicine - Open, 2020)
Background: Overtraining syndrome, caused by prolonged excessive stress, results in reduced performance and cortisol responsiveness in athletes. It is necessary to collect saliva samples sequentially within circadian rhythm for assessing exercise stress by measuring cortisol concentrations, and automated cortisol measurements using electrochemiluminescence immunoassay (ECLIA) may be useful for measuring a large number of saliva samples. In this study, we evaluated the appropriate use of cortisol-based exercise stress assessment within the circadian rhythm, which may diagnose and prevent overtraining syndrome in athletes.